Using cinema voice to promote positive intimate relationships among European youth: The Lights4Violence Project. (12th August 2022) - Neves, Sofia; Ieracitano, Francesca; Topa, Joana; Silva, Estefânia; Blanes, Maria Carmen Davó; Costa, Dália; Mocanu, Veronica; Gotcã, Ioan; Vives‐Cases, Carmen
Abstract: The paper explores the content of 61 video capsules, presenting stories about unhealthy relationships invented, performed and filmed by 534 adolescents, from Spain, Portugal, Romania and Italy. The purpose is to analyse, through a thematic analysis of the video capsules, youth perspectives on what factors, myths and beliefs turn healthy relationships into unhealthy relationships, and what positive assets are managed to solve them. The results show common youth's perspectives on the idealization of romantic love, based on gender stereotypes, identified as a common characteristic of unhealthy relationships. Individuality is misinterpreted as a threat to the stability of dating relationships. Positive assets used by victims to face dating violence (DV) are assertiveness, communication abilities and management of emotions, whereas offenders used assertiveness, empathy and critical thinking. The paper debates the efficacy of intervention programs combining youth positive development and DV prevention approaches based on filmmaking.